Seminal Extracellular Traps in SARS-CoV-2 Infection - Sardi, Melba; Repetto, Herberto; Chenlo, Patricia; Ariagno, Julia; Mendeluk, Gabriela (Journal of Clinical Nephrology, 2024)
Introduction: Extracellular Traps (ETs) are fibers composed of chromatin and cytoplasmic proteins, which can trap and kill pathogens by the phenomenon called ETosis. They are released by neutrophils, macrophages, and monocytes, and can be found in semen. The aim of this presentation is to evidence of the indirect effect of SARS-CoV-2 in semen by ETs. Patients and methods: Experimental design: retrospective descriptive observational study. Semen samples from two groups were studied following WHO guidelines: 1) SARS-CoV-2 infected donors (n: 5; at 7, 15, 30, 60, and 90 days after PCR diagnosis); 2) COVID-19 positive patients assisted in our laboratory between 2021 and 2022 (n: 70). They were observed in fresh and in Papanicolaou-stained smears by CASA and light microscopy; the presence of macrophages, spermiophages, ETs and hyperviscosity were recorded while neutrophilic concentration was calculated. Two control groups were designed: a) Patients belonging to group 2, studied before de pandemia (n: 13); b) Culture-negative semen samples (n: 28). Results: In the first group, ETs were observed in all the samples, while only 18% had leucospermia. Macrophages, spermiophages, and hyperviscosity were recorded in 68%, 27%, and 36% of the studied cases respectively. In the second group, ETs were present 100% in the acute phase (< 90 days after diagnosis) and decreased to 71% in the later stage (90 to 270 days). The trapped sperm were non-progressive motile or immotile alive or dead. No traps were found in either control group. Conclusion: In our study ETs were the most sensitive seminal marker of SARS-CoV-2 infection.